Aspects of the structure and phenology of two fynbos communities - Le Maitre, D C (Department of Biological Sciences, 2016)
Data on the floristics, biomass, pattern, growth forms and regeneration modes of two tall, mid-dense, proteoid shrublands are analysed. The phenology of a number of species in different growth forms is examined in terms of current hypotheses about growth form related timing of shoot growth, and general patterns of periodicity in nutrient-poor mediterranean environments. Taxa typical of the fynbos flora are dominant in both communities, but the drier Cedarberg community has fewer species in these taxa and more annuals than the moister Kogelberg environment. These floristic changes are reflected also in the growth form spectra and the stratification of the communities. The biomass of the cedarberg community is higher at 1820 g/m2 against 1100 g/m2 for the Kogelberg community. This difference is discussed in terms of the greater effectiveness of the rainfall at the Cedarberg (664 mm/yr), than at the Kogelberg (1016 mm/yr), and the availability of soil nutrients. There are more sprouting plants, excluding annuals, in the flora of the Cedarberg site. This is in line with the prediction that, within limits, the drier the climate, the more reliable the investment in vegetative regrowth after fire. The similarity in community physiognomy is confirmed by the quantitative analyses which show that there are differences and also strong similarities between the communities. The overstorey Proteaceae grow from spring to mid-summer, as do the Restionaceae, but the other growth forms follow a variety of patterns, including opportunistic summer growth. The sequence of phenological events is partly related to morphological sequences in plant development and partly to resource partitioning. The current hypotheses concerning community structure and phenology in mediterranean environments cannot be refuted, but they do not account for the variations observed within and between growth forms and need to be critically examined.